Evaluation von mobilen Trainingsanwendungen in der Logistik: Nutzerfeedback zur MARTINA-App - Thomas Neukirchen; Markus Kleffmann; Wilhelm Koop; Stefanie Jäger; Matthias Klumpp (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2017)
– The research project MARTINA is a cooperative endeavor of the media and creative industries and the logistics industry. Within the project, the MARTINA app, a learning platform for the logistics industry, has been developed. Prototype versions are constantly tested in various companies and contexts, the final version is supposed to offer transfer possibilities into other professional areas. The main result ("artifact") of this project is a prototypical but stand-alone executable learning application, which serves as an example of how training on the job-solutions in logistics could be established. The content, delivered via mobile app, is thus aimed at professionals from the logistics sector, e.g. truck drivers, who seem to be an exceptional match for this kind of training due to its location-independent nature. While the content of MARTINA is primarily created specifically for employees in the logistics sector, the technical realization is also transferable to other areas. MARTINA is therefore essentially a design and software development project with a focus on professional development. This research paper provides the in extenso documentation of user feedback and testing sessions during the app development phases.
Keywords: 650